2019
DOI: 10.7224/1537-2073.2018-020
|View full text |Cite
|
Sign up to set email alerts
|

Muscle Dysfunction and Walking Impairment in Women with Multiple Sclerosis

Abstract: Background: Recent evidence suggests that skeletal muscle dysfunction is involved in disability progression in people with multiple sclerosis (MS). However, the relationship between muscle dysfunction and walking impairments in MS remains unclear. Thus, the cross-sectional relationships between muscle-specific oxidative capacity and walking endurance in women with MS were evaluated. Methods: Twenty women with MS (11 African A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 43 publications
1
23
0
Order By: Relevance
“…The application of NIRS to assess bone hemodynamics and oxygenation might be expected to be based on the rather extensive literature on the use of NIRS to study skeletal muscle in both healthy (van Beekvelt et al, 2001a,b;Ryan et al, 2013a,b;Southern et al, 2014;Zhang et al, 2020) as well as in clinical populations (Abozguia et al, 2008;Sjogaard et al, 2010;Bossie et al, 2017;Willingham et al, 2019). NIRS measurements of skeletal muscle can mainly be divided into three categories: (1) measuring levels of oxygen at rest and during exercise (Hesford et al, 2013;Niemeijer et al, 2017), (2) measuring the rate of re-oxygenation after ischemia or exercise (Willingham et al, 2016;Willingham and McCully, 2017;Lucero et al, 2018), and finally (3) using short periods of repeated ischemia to measure oxidative metabolism or mitochondrial capacity (Ryan et al, 2013b;Bossie et al, 2017;Sumner et al, 2020).…”
Section: Review Of Nirs Technologymentioning
confidence: 99%
“…The application of NIRS to assess bone hemodynamics and oxygenation might be expected to be based on the rather extensive literature on the use of NIRS to study skeletal muscle in both healthy (van Beekvelt et al, 2001a,b;Ryan et al, 2013a,b;Southern et al, 2014;Zhang et al, 2020) as well as in clinical populations (Abozguia et al, 2008;Sjogaard et al, 2010;Bossie et al, 2017;Willingham et al, 2019). NIRS measurements of skeletal muscle can mainly be divided into three categories: (1) measuring levels of oxygen at rest and during exercise (Hesford et al, 2013;Niemeijer et al, 2017), (2) measuring the rate of re-oxygenation after ischemia or exercise (Willingham et al, 2016;Willingham and McCully, 2017;Lucero et al, 2018), and finally (3) using short periods of repeated ischemia to measure oxidative metabolism or mitochondrial capacity (Ryan et al, 2013b;Bossie et al, 2017;Sumner et al, 2020).…”
Section: Review Of Nirs Technologymentioning
confidence: 99%
“…Previous studies have used accelerometry to study muscle contractile function [ 22 , 23 ]. In addition, an accelerometer has been used to evaluate muscle endurance as changes in twitch contraction speeds [ 10 , 11 , 12 , 14 , 15 ]. These studies have shown a good relationship between muscle accelerometry and muscle mitochondrial capacity in clinical populations [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, an accelerometer has been used to evaluate muscle endurance as changes in twitch contraction speeds [ 10 , 11 , 12 , 14 , 15 ]. These studies have shown a good relationship between muscle accelerometry and muscle mitochondrial capacity in clinical populations [ 14 ]. Other approaches to measure muscle contractile function have used task failure in response to an applied load [ 16 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NIRS-measured mitochondrial capacity measures the transition rate of oxidative metabolism from exercise to rest, similar to methods using magnetic resonance spectroscopy to measure the rate of phosphocreatine resynthesis after exercise [ 4 , 5 ]. Mitochondrial capacity has been associated with increased muscle endurance [ 6 ].…”
Section: Introductionmentioning
confidence: 99%